Adsorption of Rhodamine B on Spherical Activated Carbon synthesized from Waste Bagasse Liquid using Hydrothermal Process (Universitas Jenderal Soedirman, 2023)
The dyes of the textile dyeing industry wastewater are harmful to humans and the environment. They should be treated before discharging into the environment. The adsorption using the spherical activated carbon can be effective to reduce the dyes. The spherical activated carbon of 3-7 µm in diameter was successfully prepared from the waste bagasse liquid using the hydrothermal method. The activation of this carbon was carried out using the KOH solution. The optimum pH and contact time were achieved in 2 and 200 min, respectively. Adsorption kinetic for RhB on activated spherical carbon follows the second-order kinetics and its adsorption mechanism follows the Langmuir isotherm. The maximum adsorption capacity of spherical activated carbon to Rhodamine B was achieved in 64.52 mg/g.